Unnamed Contracts and So-called Contracts for Saving of Life in the Roman Law - Hirata, Alessandro (Studia Warmińskie, 2014)
Freedom of contract, as defined today, has not been known in Roman Law. The Roman Law of obligations was determined by the so-called numerus clausus: in general, the parties were not allowed to conclude contracts other than those for which an actio was provided. On the other hand, this limitation could be circumvented with relative ease in legal practice. In the contract to save the life of someone, an individual receives something from another, for saving or having saved the latter from a violent, potentially lethal threat. This kind of contract serves as a good example of how the Roman jurists dealt with the freedom of contract.